A Numerical Investigation on the Structure of the Zeros of Euler Polynomials. (31st May 2015) - Ryoo, C. S.; Kang, J. Y.
Abstract : Using numerical investigation, we observe the behavior of complex roots of the Euler polynomialsE n ( x ) . By means of numerical experiments, we demonstrate a remarkably regular structure of the complex roots of the Euler polynomialsE n ( x ) . Finally, we show the Julia set of Newton iteration functionR ( x ) = x - E n ( x ) / E n ′ ( x ) .